A triphenylamine-based colorimetric and "turn-on" fluorescent probe for detection of cyanide anions in live cells1. Issue 59 (28th June 2015) - Wang, Shaodan; Xu, Hai; Yang, Qingbiao; Song, Yan; Li, Yaoxian
<x xml:space="preserve">Abstract</x> A triphenylamine–hemicyanine dye was developed as a colorimetric and turn-on fluorescent probe for detection of cyanide with high sensitivity and selectivity.